Dimensional response analysis of yielding structures with first-mode dominated response. - Makris, Nicos (Earthquake engineering & structural dynamics.)
This paper introduces a new way of estimating the inelastic response of first-mode dominated structures with behaviour that can be approximated with the elastoplastic idealization. The proposed approach emerges from formal dimensional analysis and is liberated from the response of the elastic system. The application of the proposed method hinges upon the existence of a distinct time scale and a length scale that characterize the most energetic component of the ground shaking. Such time and length scales emerge naturally from the distinguishable pulses which dominate a wide class of strong earthquake records; they are directly related with the rise time and slip velocity of faulting, and can be formally extracted with validated mathematical models published in the literature. The most decisive feature of this work is that the inelastic response curves that result with the proposed approach assume similar shapes for different values of the normalized yield displacement. Because of this similarity the paper proposes a single inelastic response curve which offers directly the maximum inelastic displacement of the structure given the energetic pulse period and pulse amplitude of the ground shaking. When the proposed method is applied to MDOF structures it is not capable to estimate interstorey drifts nor is capable to capture the effects of negative stiffness which may result due to P-delta effect.